A Changing Art. Nineteenth-Century Painting Practice and Conservation - Bruquetas Galán, Rocío (Ge-conservacion, 2018)
A Changing Art. Nineteenth-Century Painting Practice and Conservation Ed. Por Nicola Costaras, Kate Lowry, Helen Glanville, Pippa Balch, Victoria Sutcliffe y Polly Satlmarsh) Londres: Archetype (en asociación con The British Association of Paintings Conservator-Restorers, BAPCR), 2017. ISBN: 9781909492547 Dimensiones: 246 x 175 mm Páginas: 144 Ilustraciones en color